Preparing Apigenin from Leaves of Adinandra nitida - Zhengxiang Ning; Jianhua Gao; Keyong Xu; Benguo Liu (Food Technology and Biotechnology, 2008)
Leaves of Adinandra nitida were used as raw material, and a new industrially significant method of preparing apigenin was established by hydrolyzing a water extract and recrystallizing it with ethanol in order to obtain a new source for the production of this flavone. A yield of about 2.5 % (dry mass) was obtained with the purity of 93.05 %, determined by high performance liquid chromatography (HPLC). Moreover, the main flavonoids in leaves of Adinandra nitida and the product after acid hydrolysis were identified as camellianin A and apigenin, respectively, by ultraviolet-visible spectrometry (UV/VIS) and electrospray ionization mass spectrometry (ESI-MS).